Development and Validation of Analytical Methods for Radiochemical Purity of 177Lu-PSMA-1 - Pauline Orhon; Marie-Dominique Desruet; Marie Piquemal; Nicolas De Leiris; Loïc Djaileb; Jean-Philippe Vuillez; Pierrick Bedouch; Julien Leenhardt (MDPI AG, 2022)
Prostate Specific Membrane Antigen (PSMA) is a highly relevant target in nuclear medicine due to its overexpression in prostate cancer. The 68Ga/177Lu-PSMA-1 combination is a theranostic agent for the detection and treatment of tumors overexpressing the PSMA target. Specifically, 177Lu-PSMA-1 is used in the treatment of castration-resistant prostate cancer that is ineffective or intolerant to the latest generation of chemotherapy and/or hormone therapy. This radiopharmaceutical is manufactured in a radiopharmaceutical synthesizing unit and must pass a quality control where the radiochemical purity (RCP) is assessed prior to release of the batch. RCP evaluation is performed by high-performance liquid chromatography (HPLC) and thin-layer chromatography (TLC). Since there is no monograph for 177Lu-PSMA-1 in the European Pharmacopoeia, we validate the analytical methods according to the EANM recommendations adapted from ICH Q2. Specificity, linearity, accuracy, precision, intermediate precision, limit of quantification (LOQ) and robustness were described for HPLC and TLC in this study. The results obtained demonstrated the robustness and reliability of the HPLC and TLC analytical methods for the evaluation of the RCP of 177Lu-PSMA-1.